Combined NMR analysis of huge residual dipolar couplings and pseudocontact shifts in terbium(III)-phthalocyaninato single molecule magnets - Damjanović, Marko; Katoh, Keiichi; Yamashita, Masahiro; Enders, Markus (Journal of the American Chemical Society, 2013)
Several small paramagnetic complexes combine large hyperfine NMR shifts with large magnetic anisotropies. The latter are a prerequisite for single molecule magnet (SMM) behavior. We choose the SMM tris(octabutoxyphthalocyaninato) diterbium (1) for a high resolution NMR study where we combined for the first time a comprehensive 1H and 13C chemical shift analysis of a SMM with the evaluation of large residual dipolar couplings (RDCs). The latter are a consequence of partial alignment of SMM 1 in the strong magnetic field of the NMR spectrometer. To the best of our knowledge RDCs in SMMs have never been reported before. We measured RDCs between −78 and +99 Hz for the 13C-1H vectors of CH bonds and up to −109 Hz for 1H-1H vectors of geminal hydrogen atoms (magnetic field of 14.09 T, temperature 295 K). Considerable negative Fermi contact shifts (up to −60 ppm) were determined for 13C atoms at the phthalocyaninato core. Paramagnetic 13C NMR shifts of the butoxy chains as well as all 1H NMR chemical shifts are a result of pseudocontact shifts (pcs), and therefore it is easily possible to determine the positions of the respective nuclei in solution. Measurements of CH and HH vectors by RDC analysis are in accordance with the geometry as determined by the pseudocontact shifts, but in addition to that, RDCs give information about internal mobility. The axial component of the magnetic susceptibility tensor has been determined independently by pcs and by RDC.
Gesehen am 02.06.2021